Individually-Personal Peculiarities of Younger Preschoolers' Speech - M E Novikova (Peoples' Friendship University of Russia (RUDN University), 2013)
Studying the speech of the younger preschoolers is a major factor in designing educational methods and preparing children for school. There exist individual and gender differences in the way children acquire speech skills. Word comprehension and idea interpretation depend on the child's upbringing, his or her environment, the interaction within the family. This article submits the research data obtained from the study of the individual peculiarities of the younger preschool children's speech.